2018
DOI: 10.1111/apa.14373
|View full text |Cite
|
Sign up to set email alerts
|

Outpatients with acute osteoarticular infections had favourable outcomes when they received just oral antibiotics without intravenous antibiotics

Abstract: Outpatients with OAI who were in good general health had favourable outcomes when they received oral antibiotics without intravenous antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 20 publications
0
25
0
2
Order By: Relevance
“…Trimethoprim/sulfamethoxazole could be used to manage osteomyelitis, even as monotherapy, when the clinical condition is stable [ 10 , 21 , 38 , 39 , 46 49 ]. This drug represents an attractive option due to its anti-MRSA activity: time-kill kinetic studies have demonstrated bactericidal action at concentrations four times higher than the MIC.…”
Section: Oral Antibiotic Therapymentioning
confidence: 99%
“…Trimethoprim/sulfamethoxazole could be used to manage osteomyelitis, even as monotherapy, when the clinical condition is stable [ 10 , 21 , 38 , 39 , 46 49 ]. This drug represents an attractive option due to its anti-MRSA activity: time-kill kinetic studies have demonstrated bactericidal action at concentrations four times higher than the MIC.…”
Section: Oral Antibiotic Therapymentioning
confidence: 99%
“…Las publicaciones que comparan los pacientes con IOA por K. kingae con las otras etiologías, reportaron un menor requerimiento de procedimientos quirúrgicos, menos días de internación y mejor evolución 17,18 . En el estudio realizado, los pacientes con IOA también tuvieron menos días de internación, valor de PCR cuantitativa inicial menor y una normalización más temprana.…”
Section: Experiencia Clínicaunclassified
“…Alcobendas y cols. 18 , reportaron la buena evolución clínica con la administración de un tratamiento exclusivamente por vía oral a 25 niños con IOA, donde K. kingae fue la etiología predominante.…”
Section: Experiencia Clínicaunclassified
“…In conclusion, we found that the report by Alconbendas et al was interesting and thought‐provoking. There is no doubt that many bone and joint infections can be treated solely with oral antibiotics, but only sufficiently powered prospective and randomised studies will teach us to what extent the findings of this preliminary investigation can be generalised.…”
mentioning
confidence: 99%
“…In this issue of Acta Paediatrica , Alcobendas et al from Madrid present their results of 25 children with an osteoarticular infection who were treated as outpatients and only received oral antibiotics. They gave them maximum doses of cephalosporin, amoxicillin‐clavulanate or clindamycin for a median duration of 21 days, but did not state how high the doses actually were.…”
mentioning
confidence: 99%